Prevalence of Myths and False Beliefs Regarding HIV/AIDS among Xhosa Community in the Transkei Region of South Africa - BL Meel (Institute of Medico-legal Publications Pvt Ltd, 2020)
HIV/AIDS is one of the main challenges facing South Africa today. It is estimated that of the 39.5 millionpeople living with HIV worldwide in 2006, more than 63% were from sub-Saharan Africa. In 2005, about5.54 million people were estimated to be living with HIV in South Africa, with 18.8% of the adult population(15-49 years) and about 12% of the general population affected.1Prevention of HIV infection has to be tackled in various ways, not just to recommend condom use andcircumcision. There are several cultural and social factors associated with spread of HIV infection. Thereis a general belief that illness (HIV/AIDS) and other bad occurrences are related to witchcraft. The illnessis difficult for them to believe and to be explained. Infections like HIV cannot be explained to ordinaryrural people and therefore there is a strong belief in witchcraft. People believe that HIV/AIDS is relatedto witchcraft, and could be managed by traditional healers. Poor people are less educated and thereforemore ignorant about their illnesses. Most of young deaths where the deceased is sick from a long time werelabeled as “Isidliso” otherwise called “black poison”. Almost everybody who is suffering from HIV/AIDShas been taken to a traditional healer before been taken to medical practitioner in town. The widespread rapeand forced sexual abuse of children is a serious social and health issue. There are several motives behind thisunsocial and unhealthy epidemic, but the most dangerous is the strong belief in a myth of achieving a curefor a person’s HIV/AIDS through sexual intercourse with a virgin.